Household Moderation as a Foundation for Building a Harmonic Family: An Integration of Murray Bowen's Family Systems Theory and Maqashid Sharia - Sugitanata, Arif (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2024)
This study explores the concept of "household moderation" as a strategy to overcome the dynamics and challenges of family life. This research adopts a literature-based qualitative research type to analyze the concept of household moderation. By integrating Murray Bowen's Family Systems theory and Maqashid Shariah principles, this research shows that household moderation, through practices such as prudent financiafl planning, equitable division of tasks, effective time management, education, and physical and mental health, can create a strong foundation for a harmonious and supportive family life. This research emphasizes the importance of effective communication, cooperation and flexibility in dealing with daily challenges and adapting to changes in family life. Based on an analysis of Murray Bowen's Family Systems theory, home moderation offers insights into how self-differentiation, avoidance of negative triangulation and stabilization of the family emotional system can support healthy family functioning. In addition, marital moderation also contributes to protecting the five aspects of essential well-being according to Maqashid Shariah: religion, soul, intellect, offspring and property. However, this study also recognizes the need to explore further the application of household moderation in highly diverse family contexts to enhance the relevance and applicability of this concept in a pluralistic society.